Efeitos do exercício físico sobre a atividade de enzimas que degradam nucleotídeos e nucleosídeo de adenina em pacientes com síndrome metabólica - Martins, Caroline Curry (2016)
Metabolic syndrome (MetS) is a condition characterized by the presence of multiple cardiovascular risk factors such as hypertension, hyperglycemia, hyperlipidemia and abdominal obesity. The association of these factors provides pro-thrombotic and pro-inflammatory conditions, which contribute to the atherosclerosis process. Platelet aggregation and the immune-inflammatory response are governed by several mechanisms, including the purinergic signaling way extracellular adenine nucleotides (ATP, ADP, and AMP) and nucleoside. Extracellular levels of these molecules and the consequent control of purinergic signaling induced by them is performed by enzymes such as E-NTPDases (Ecto-nucleotide Triphosphate Difosfoidrolases), E-NPPs (Ecto-Nucleotide Pyrophosphatase/Phosphodiesterases), E-5'-nucleotidase and ADA (Adenosine Deaminase). Studies have shown that exercise training promotes the production of adenosine and controls the ATP and ADP levels, decreasing the harmful effects on the cardiovascular system. By comparison, it has been observed a series of beneficial actions and cardioprotective effects of exercise training on MetS. In this context, the aim of this study was to verify the effect of the regular practice of physical exercise on the activity of the purinergic enzymes in platelets and lymphocytes, as well as on platelet aggregation and inflammatory markers of the MetS patients. These parameters were evaluated in MetS patients (n = 38) at the time of diagnosis and after 30 weeks of a concurrent physical exercises plan, practiced 3 times a week. All parameters were also measured in a group of healthy subjects (n = 30) without exercise intervention. The obtained results demonstrated significant increase in the activity of the E-NTPDase, E-NPP and E-5'-nucleotidase enzymes, and decrease in the activity of the ADA enzyme in platelets of MetS patients, accompanied by an increase in platelet aggregation. Similarly, in lymphocytes, the E-NTPDase activity was increased and ADA activity was diminished, concomitant to an elevation in the levels of inflammatory markers in MetS group. On the other hand, the regular practice of exercise training was able to revert these changes at the end of the 30-weeks of training, returning the enzymatic activities to the basal level or close to it in both platelets and lymphocytes. Similarly, platelet aggregation, inflammatory markers and the anthropometric and biochemical parameters also returned to normal levels after the 30 weeks. After 15 weeks of the exercise training it was observed an improvement in the enzymatic activities in lymphocytes and in biochemical and inflammatory parameters of MetS patients, but the results did not reach basal levels. Thus, the results described here suggest that the purinergic enzymes have significant functions in SMet, with cardioprotective effects and participation in the control of metabolic imbalance; and their measure could serve as inflammatory, thrombotic and metabolic markers. Additionally, the regular exercise training plays important roles of metabolic regulation and anti-trombóticos and anti-inflammatory effects by modulating the activity of enzymes of the purinergic system in MetS. It is also concluded that the long-term and regular practice are essential to obtain the beneficial effects of exercise training on the MetS condition.